Nepal : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2010)
Over the past several years, Nepal has pursued a prudent fiscal policy, which has resulted in a significant reduction of public debt as a percentage of GDP. This paper reexamines the fiscal stance in Nepal in light of recent developments. The optimal level of the fiscal deficit is constrained by the need to achieve and sustain a debt-to-GDP ratio with an acceptable level of vulnerability to distress. The debt sustainability analyses (DSA) framework focuses on the net present value (NPV) of external public and publicly guaranteed debt, though public debt is also analyzed.